The Qur’anic Structure as an Alternative Healing Method: A Case Study of Healing Practices in the Jakarta Qur’anic Structure Studies Community (International Journal of Education and Literature, 2025)
This study investigates Qur’an-based healing practices within the Jakarta Qur’anic Structure Studies Community, focusing on the understanding of the Qur’an as Asy-Syifā’ (a source of healing) and the therapeutic application of Qur’anic verses through the Qur’anic Structure method. Employing a qualitative, descriptive-analytical design within a Living Qur’an and phenomenological framework, data were collected through participant observation, in-depth interviews with three key informants, and questionnaires administered to 23 practitioners. The findings show that the community positions the Qur’anic Structure method as an alternative approach to both physical and spiritual healing by treating the entire Qur’an as a medium of cure. This practice is operationalized through four principal patterns: the ‘Ain Structure, Page Structure, Alphabet Structure, and Surah Structure, all of which refer to the 18-line mushaf published by PT Taj Company (Karachi, Pakistan). Practitioners’ testimonies indicate perceived improvements in physical and psychological conditions, framing this method as a form of Qur’anic self-healing (ikhtiar) while reaffirming that ultimate healing belongs solely to Allah SWT.